Perovskite solar cell capable of inhibiting lead leakage and preparation method thereof
By doping APUS molecules into the light absorbing layer of perovskite solar cells and exterior packaging, the problem of lead leakage under extreme conditions is solved, effective adsorption of lead and leakage suppression is achieved, and the biocompatibility of the battery is improved.
Patent Information
- Application Number
- CN202411877981.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing perovskite solar cells are prone to lead leakage in extreme weather and fires, causing ecological and health threats.
By doping APUS molecules into the light absorbing layer of a perovskite solar cell and encapsulating it outside the battery, a modified perovskite light absorbing layer and APUS molecular thin film are formed to achieve adsorption of lead and suppression of leakage.
It effectively inhibits lead leakage in perovskite films, improves the biocompatibility of solar cells, and significantly reduces the leakage concentration of lead in acid rain simulation tests.
Smart Images

Figure CN119789662A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of perovskite solar cells, and in particular to a perovskite solar cell with lead leakage inhibition and a preparation method thereof. Background Art
[0002] In recent years, organic-inorganic hybrid perovskite solar cells (PSCs) have attracted widespread attention due to their excellent photoelectric conversion efficiency (25.7%), simple preparation process and low manufacturing cost, becoming one of the photovoltaic technologies with commercial application prospects. However, extreme weather conditions such as hail, high temperature and running water, as well as emergencies such as fire, can cause perovskite films to leak PbI2 and Pb 0 Lead-containing toxic heavy metal products such as PbO pose a serious threat to the ecosystem and human health. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the present invention provides a perovskite solar cell capable of suppressing lead leakage and a method for preparing the same.
[0004] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:
[0005] Provided is a perovskite solar cell for inhibiting lead leakage, wherein a modified perovskite light-absorbing layer of the perovskite solar cell is prepared by doping with APUS molecules, and the APUS molecular structure is shown in Formula I;
[0006]
[0007] Furthermore, the perovskite solar cell is externally encapsulated using a thin film made from APUS molecules.
[0008] Furthermore, the thickness of the film prepared by APUS molecules is 3 mm.
[0009] The present invention also provides a method for preparing the above-mentioned perovskite solar cell for inhibiting lead leakage, comprising the following specific steps:
[0010] S1: Preparation of SnO2 electron transport layer on ITO glass substrate;
[0011] S2: A two-step method is used to prepare a modified perovskite light absorbing layer on the SnO2 electron transport layer. First, a PbI2 film is prepared on the SnO2 electron transport layer;
[0012] S3: preparing a modified film on the PbI2 film, specifically: dissolving methylammonium chloride, methylammonium bromide and formamidine hydroiodide in isopropanol at room temperature to obtain a mixed solution A; dissolving APUS molecules in dimethylacetamide at room temperature to obtain a mixed solution B; mixing the mixed solution B and the mixed solution A at a volume ratio of 1:100, spin coating the mixed solution on the PbI2 film, and annealing the mixed solution on a hot plate at 140°C for 10 minutes to obtain a modified perovskite light-absorbing layer;
[0013] S4: Prepare a Spiro-OMeTAD hole transport layer on the surface of the modified perovskite light absorbing layer;
[0014] S5: Evaporate a metal electrode on the surface of the Spiro-OMeTAD hole transport layer.
[0015] Furthermore, the mass ratio of methylammonium chloride, methylammonium bromide and formamidine hydroiodide in mixed solution A is 6:6:60, and the dosage ratio of methylammonium chloride to isopropanol is 6 mg:1 mL; the dosage ratio of APUS molecule to dimethylacetamide in mixed solution B is 10 mg:1 mL.
[0016] Furthermore, the ratio of the volume of the mixed solution after the mixed solution B and the mixed solution A were mixed to the area of the PbI2 film was 130 μL / 256 mm 2 .
[0017] Furthermore, step S1 is specifically as follows:
[0018] S11: uniformly dispersing SnO2 water-soluble colloid with a mass fraction of 12% in deionized water by ultrasonication to obtain a SnO2 aqueous solution; the volume ratio of the SnO2 water-soluble colloid to the deionized water is 1:6;
[0019] S12: filtering the SnO2 aqueous solution using a polyethersulfone filter with a filter diameter of 0.22 μm to obtain a SnO2 filtrate;
[0020] S13: The SnO2 filtered liquid was dropped onto the ITO glass substrate, and the substrate was spin-coated at a rotation speed of 4000 rpm / s for 30 seconds, and annealed at 180° C. for 20 minutes to obtain a SnO2 electron transport layer.
[0021] Furthermore, the specific steps of preparing the PbI2 thin film on the SnO2 electron transport layer are:
[0022] S21: PbI2 was dissolved in a mixed solution of dimethyl sulfoxide and N,N-dimethylformamide at 60°C, and heated and stirred for 3 hours; the volume ratio of dimethyl sulfoxide to N,N-dimethylformamide was 50:950; the amount ratio of PbI2 to dimethyl sulfoxide was 0.6 g:50 μL;
[0023] S22: After the heating reaction is completed, the temperature is lowered to room temperature and filtered through PTFE with a filter diameter of 0.22 μm to obtain a PbI2 solution;
[0024] S23: PbI2 solution was added dropwise onto the SnO2 electron transport layer, and the solution was spin coated at a speed of 1500 rpm / s for 30 s. The PbI2 film was annealed at 65 °C for 1 min. The ratio of the PbI2 solution to the SnO2 electron transport layer area was 50 μL / 256 mm 2 .
[0025] Furthermore, step S4 is specifically as follows:
[0026] S41: After dissolving Spiro-OMeTAD in chlorobenzene, add tributyl phosphate and lithium salt solution, and stir to react for 2h;
[0027] S42: After the reaction is completed, the Spiro-OMeTAD solution is filtered using PTFE with a filter diameter of 0.22 μm;
[0028] S43: The Spiro-OMeTAD solution was dropped onto the surface of the modified perovskite light absorbing layer, and spin coated at a rotation speed of 4500 rpm for 30 seconds to obtain the Spiro-OMeTAD hole transport layer.
[0029] Further, in step S5, the metal evaporated on the surface of the Spiro-OMeTAD hole transport layer is Au or Ag. When the evaporated metal is Au, The average evaporation rate of 70nm metal electrode was evaporated on the surface of Spiro-OMeTAD hole transport layer; when the evaporated metal was Ag, The average evaporation rate of a 100nm metal electrode was evaporated on the surface of the Spiro-OMeTAD hole transport layer.
[0030] The beneficial effects of the present invention are:
[0031] The present invention adopts APUS molecules to prepare the modified perovskite light-absorbing layer, which can achieve the adsorption of lead, thereby effectively inhibiting the lead leakage of the perovskite film, and the film made of APUS molecules is used to externally encapsulate the battery, thereby achieving the inhibition of lead leakage both inside and outside. The biocompatibility of the organic-inorganic hybrid perovskite solar cell is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a comparison of XPS spectra of perovskite films doped with and without APUS;
[0033] Figure 2 This is a comparison of the FTIR spectra of whether APUS is combined with PbI2;
[0034] Figure 3 This is a comparison of the Raman spectra of whether APUS is bound to PbI2;
[0035] Figure 4 Comparison of PL spectra of perovskite films doped with and without APUS;
[0036] Figure 5 Schematic diagram of the APUS internal and external co-encapsulated perovskite battery structure;
[0037] Figure 6 This is a comparison chart of the efficiency of batteries with and without APUS doping.
[0038] Figure 7 For specific implementation
[0039] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0040] Example 1 Preparation of APUS molecule-doped modified perovskite light-absorbing layer
[0041] The specific steps are:
[0042] S1: SnO2 electron transport layer was prepared on an ITO glass substrate purchased from South China Xiangcheng Technology; the performance size of the ITO glass substrate is 6Ωsq -1 ,16.1mm×16.1mm, before preparing the SnO2 electron transport layer, the ITO glass substrate was cleaned. The specific operation was to use a cotton swab dipped in a detergent solution to scrub vigorously to remove the oil and impurities on the surface of the substrate, and then place the wiped substrate in a polytetrafluoroethylene (PTFE) basket and ultrasonicate in a detergent solution, a DI solution and an ethanol solution for 20 minutes to remove the impurities and residual organic matter on the surface of the substrate. Finally, a nitrogen gun was used to purge the ethanol on the surface of the substrate to obtain a clean ITO glass substrate.
[0043] The specific steps for preparing the SnO2 electron transport layer are:
[0044] S11: 12% SnO2 water-soluble colloid purchased from Braite was uniformly dispersed in deionized water by ultrasonic treatment to obtain SnO2 aqueous solution, and the ultrasonic treatment time was 30 min; during the ultrasonic treatment, the clean ITO glass substrate was treated in a UV ozone cleaning machine for 20 mins to completely remove organic matter on the substrate surface and increase the wettability of the substrate surface; the volume ratio of SnO2 water-soluble colloid to deionized water was 1:6;
[0045] S12: filtering the SnO2 aqueous solution using a polyethersulfone filter with a filter diameter of 0.22 μm to obtain a SnO2 filtrate;
[0046] S13: 150 μL of SnO2 filtrate was dropped onto the ITO glass substrate, and the mixture was spin-coated at a rotation speed of 4000 rpm / s for 30 seconds, and annealed at 180°C for 20 minutes to obtain a SnO2 electron transport layer. The SnO2 electron transport layer and the ITO glass substrate were used as an ITO / SnO2 substrate for subsequent preparation;
[0047] S2: A modified perovskite light absorbing layer is prepared on the SnO2 electron transport layer by a two-step method. First, a PbI2 film is prepared on the SnO2 electron transport layer. The specific steps are:
[0048] S21: 0.5993 g of PbI2 was weighed and dissolved in a mixed solution of dimethyl sulfoxide and N,N-dimethylformamide at 60°C, and heated and stirred for 3 h; the mixed solution included 50 μL of dimethyl sulfoxide and 950 μL of N,N-dimethylformamide;
[0049] S22: After the heating reaction is completed, the temperature is lowered to room temperature and filtered through PTFE with a filter diameter of 0.22 μm to obtain a PbI2 solution;
[0050] S23: Treat the prepared ITO / SnO2 substrate in a UV ozone cleaner for 5 minutes to improve its surface wettability and facilitate solution spreading, pipette 50 μL of PbI2 solution and drop it on the SnO2 electron transport layer, spin coat at a speed of 1500 rpm / s for 30 seconds, and anneal at 65°C for 1 minute to obtain the PbI2 thin film.
[0051] S3: preparing a modified film on the PbI2 film, specifically: weighing 6 mg of methylammonium chloride, 6 mg of methylammonium bromide and 60 mg of formamidine hydroiodide and dissolving them in 1 mL of isopropanol at room temperature to obtain a mixed solution A; and filtering through 0.22 μm PTFE to obtain a clear solution A;
[0052] Weigh 10 mg of APUS molecule, and the synthesis method of APUS molecule is synthesized according to the technology disclosed in the prior art Yao W, Sui X, Yang D, et al. "Versatile Photoluminescence Polymers for Printed Transparent Self-Healing Optical Devices[J]. Advanced Functional Materials, 2023, 34(17):"; dissolve in 1 mL of dimethylacetamide at room temperature to obtain a mixed solution B; mix the mixed solution B and the clarified solution A in a volume ratio of 1 μL: 100 μL, transfer 130 μL and spin coat it on the PbI2 film, place it on a hot stage at 140°C and anneal for 10 minutes to obtain a modified perovskite light-absorbing layer; in the specific implementation, the annealing environment is air with a humidity of 30-40%.
[0053] A control group (Control) was set up. The difference between the control group and the modified perovskite light-absorbing layer was that when preparing the control group, dimethylacetamide was directly used to mix evenly with the clear solution A in a volume ratio of 1 μL:100 μL, and 130 μL was transferred and spin-coated on the PbI2 film. The other parameters were consistent with the above steps S1-S3.
[0054] The control group and the modified perovskite light absorbing layer were tested by X-ray photoelectron spectroscopy (XPS), and the results were as follows: Figure 1 As shown by Figure 1 It can be seen that compared with the control group, the binding energy shift of the Pb4f peak of the APUS-modified perovskite film is lower, indicating that the electron cloud density of Pb and I increases and APUS molecules form bonds during the crystallization process. This can be attributed to the abundant active sites on APUS, which effectively bind to Pb 2+ Interaction and combination, thus achieving efficient passivation of perovskite and Pb 2+ Anchoring.
[0055] The modified perovskite light absorbing layer (APUS-Pb) and APUS film were tested by Fourier transform infrared absorption spectroscopy (FTIP). Figure 2 As shown by Figure 2 It can be seen that after APUS interacts with PbI2, the stretching vibration peak of NH in APUS shifts, indicating that the NH on APUS interacts with Pb 2+ There is a strong interaction between them.
[0056] Raman spectroscopy was performed on the modified perovskite light absorbing layer (APUS-Pb) and APUS film. The results are as follows Figure 3 As shown by Figure 3It can be seen that after APUS interacts with PbI2, the -1 ~600cm -1 The SS bond of APUS was significantly shifted, indicating that the SS bond of APUS and Pb 2+ There is a strong interaction between them.
[0057] The photoluminescence spectrum (PL) of the control group and the modified perovskite light absorbing layer was tested, and the results are as follows Figure 4 As shown by Figure 4 It can be seen that the perovskite film prepared by doping APUS has a stronger luminescence intensity.
[0058] Example 2 Preparation of perovskite solar cells with suppressed lead leakage
[0059] The modified perovskite light-absorbing layer prepared in Example 1 was used to prepare a perovskite solar cell for inhibiting lead leakage by the following method:
[0060] S41: Weigh 72.3 mg of Spiro-OMeTAD, dissolve it in 1 mL of chlorobenzene and stir evenly. Then add 28.8 μL of tributyl phosphate and 17.5 μL of lithium salt solution, stir and react for 2 hours; in the specific implementation, the lithium salt solution is prepared by dissolving 520 mg of LiTFSI in 1 mL of acetonitrile;
[0061] S42: After the reaction is completed, the Spiro-OMeTAD solution is filtered using PTFE with a filter diameter of 0.22 μm;
[0062] S43: Take 25 μL of the filtered Spiro-OMeTAD solution and drop it on the surface of the modified perovskite light-absorbing layer, and spin-coat it at a speed of 4500 rpm for 30 seconds to obtain the Spiro-OMeTAD hole transport layer.
[0063] S5: The metal evaporated on the surface of the Spiro-OMeTAD hole transport layer is Au. The average evaporation rate is 70nm on the surface of the Spiro-OMeTAD hole transport layer. In the specific implementation, the evaporated metal can also be Ag. When the evaporated metal is Ag, The average evaporation rate of 100nm of metal electrode was evaporated on the surface of Spiro-OMeTAD hole transport layer. The structure of the obtained perovskite solar cell with suppressed lead leakage is shown in Figure 2. Figure 5 As shown, Au is a metal electrode, HTL is a Spiro-OMeTAD hole transport layer, Perovskite is a modified perovskite light absorbing layer, ETL is a SnO2 electron transport layer, ITO is an ITO glass substrate, and APUS is an APUS molecular film attached to the upper and lower sides of the perovskite solar cell thin film device.
[0064] During specific implementation, a 3mm thick APUS molecular film can also be attached to the upper and lower sides of the perovskite solar cell to achieve external packaging of the device; in this embodiment, an unpackaged battery (C) is provided: a device prepared by using the control group in Example 1 and S41-S43 and S5; only an internally packaged battery (I-APUS): that is, the battery prepared in the above step S5; only an externally packaged battery (E-APUS): obtained by attaching a 3mm thick APUS molecular film to the upper and lower sides of the unpackaged battery; a collaborative internal and externally packaged battery (G-APUS): obtained by attaching a 3mm thick APUS molecular film to the upper and lower sides of the battery that is only internally packaged.
[0065] The above four groups of devices were subjected to acid rain simulation tests. The specific operation was: pH = 4.2 nitric acid solution was dripped on the damaged panel at a flow rate of 10mL / h for 1h to simulate acid rain erosion. The battery after acid rain erosion was tested by inductively coupled plasma atomic emission spectroscopy. The results are as follows: Figure 6 As shown by Figure 6 It can be seen that the Pb ion content in the contaminated water of C, E-APUS and I-APUS is 2.09ppm, 0.65ppm and 0.49ppm respectively, while G-APUS reduces the average lead concentration to 0.38ppm. The battery I-APUS prepared by APUS molecule doping can effectively inhibit the leakage of lead, and adopts internal and external coordinated packaging, which can have a lead storage efficiency of up to 81.77%.
[0066] The efficiency of the unpackaged battery (C) and the internal packaged battery only (I-APUS) was tested, and the results are as follows Figure 7 As shown by Figure 7 It can be seen that the performance of the battery prepared by APUS molecule doping is almost the same as that of the undoped battery, and the doping of APUS molecules will not affect the performance of the battery.
Claims
1. A perovskite solar cell with suppressed lead leakage, characterized in that: The modified perovskite light-absorbing layer of the perovskite solar cell is prepared by doping with APUS molecules, and the APUS molecular structure is shown in Formula I; 2. The lead leakage inhibiting perovskite solar cell according to claim 1, characterized in that: The perovskite solar cell is externally encapsulated using a thin film made of APUS molecules.
3. The lead leakage inhibiting perovskite solar cell according to claim 2, characterized in that: The thickness of the film prepared by the APUS molecules is 3 mm.
4. The method for preparing a lead leakage inhibiting perovskite solar cell according to claim 1, characterized in that: The specific steps include: S1: Preparation of SnO2 electron transport layer on ITO glass substrate; S2: A two-step method is used to prepare a modified perovskite light absorbing layer on the SnO2 electron transport layer. First, a PbI2 film is prepared on the SnO2 electron transport layer; S3: preparing a modified film on the PbI2 film, specifically: dissolving methylammonium chloride, methylammonium bromide and formamidine hydroiodide in isopropanol at room temperature to obtain a mixed solution A; dissolving APUS molecules in dimethylacetamide at room temperature to obtain a mixed solution B; mixing the mixed solution B and the mixed solution A at a volume ratio of 1:100, spin coating the mixed solution on the PbI2 film, and annealing the mixed solution on a hot plate at 140°C for 10 minutes to obtain a modified perovskite light-absorbing layer; S4: Prepare a Spiro-OMeTAD hole transport layer on the surface of the modified perovskite light absorbing layer; S5: Evaporate a metal electrode on the surface of the Spiro-OMeTAD hole transport layer.
5. The preparation method according to claim 4, characterized in that: The mass ratio of methylammonium chloride, methylammonium bromide and formamidine hydroiodide in the mixed solution A is 6:6:60, and the dosage ratio of methylammonium chloride to isopropanol is 6 mg:1 mL; the dosage ratio of APUS molecules to dimethylacetamide in the mixed solution B is 10 mg:1 mL.
6. The preparation method according to claim 4, characterized in that: The ratio of the volume of the mixed solution after the mixed solution B and the mixed solution A are mixed to the area of the PbI2 film is 130 μL / 256 mm 2 .
7. The preparation method according to claim 4, characterized in that: The step S1 is specifically as follows: S11: uniformly dispersing SnO2 water-soluble colloid with a mass fraction of 12% in deionized water by ultrasonication to obtain a SnO2 aqueous solution; the volume ratio of the SnO2 water-soluble colloid to the deionized water is 1:6; S12: filtering the SnO2 aqueous solution using a polyethersulfone filter with a filter diameter of 0.22 μm to obtain a SnO2 filtrate; S13: The SnO2 filtered liquid was dropped onto the ITO glass substrate, and the substrate was spin-coated at a rotation speed of 4000 rpm / s for 30 seconds, and annealed at 180° C. for 20 minutes to obtain a SnO2 electron transport layer.
8. The preparation method according to claim 4, characterized in that: The specific steps for preparing PbI2 thin film on SnO2 electron transport layer are: S21: PbI2 is dissolved in a mixed solution of dimethyl sulfoxide and N,N-dimethylformamide at 60°C, and heated and stirred for 3 hours; the volume ratio of dimethyl sulfoxide to N,N-dimethylformamide is 50:950; the amount ratio of PbI2 to dimethyl sulfoxide is 0.6 g:50 μL; S22: After the heating reaction is completed, the temperature is lowered to room temperature and filtered through PTFE with a filter diameter of 0.22 μm to obtain a PbI2 solution; S23: PbI2 solution was dropped onto the SnO2 electron transport layer, and the solution was spin-coated at a speed of 1500 rpm / s for 30 seconds, and annealed at 65°C for 1 minute to obtain a PbI2 thin film; the ratio of the PbI2 solution to the SnO2 electron transport layer area was 50 μL / 256 mm 2 .
9. The preparation method according to claim 4, characterized in that: The step S4 is specifically as follows: S41: After dissolving Spiro-OMeTAD in chlorobenzene, add tributyl phosphate and lithium salt solution, and stir to react for 2h; S42: After the reaction is completed, the Spiro-OMeTAD solution is filtered using PTFE with a filter diameter of 0.22 μm; S43: The Spiro-OMeTAD solution was dropped onto the surface of the modified perovskite light absorbing layer, and spin coated at a rotation speed of 4500 rpm for 30 seconds to obtain the Spiro-OMeTAD hole transport layer.
10. The preparation method according to claim 4, characterized in that: In step S5, the metal evaporated on the surface of the Spiro-OMeTAD hole transport layer is Au or Ag. When the evaporated metal is Au, The average evaporation rate of 70nm metal electrode was evaporated on the surface of Spiro-OMeTAD hole transport layer; when the evaporated metal was Ag, A 100nm thick metal electrode was deposited on the surface of the Spiro-OMeTAD hole transport layer at an average evaporation rate of .
Citation Information
Patent Citations
Novel polyurethane and application thereof
CN113817123A
Sulfonic acid compound-doped modified three-dimensional hybrid perovskite solar cell prepared based on two-step method
CN115915779A
Method for preparing efficient perovskite solar cell and perovskite solar cell
CN118678840A